Evaluation of triticale genotypes under low land conditions in the State of São Paulo, Brazil - Felicio, João Carlos; Camargo, Carlos Eduardo de Oliveira; Gallo, Paulo Boller; de Camargo, Marcelo Bento Paes (Pesquisa Agropecuaria Brasileira, 1995)
Experiments involving triticale genotypes carried out under low land conditions, at the Mococa Experiment Station, in Mococa, SP, Brazil, during 1985-92, were evaluated in relation to grain yield and to the occurrence of sterile spikelets. The triticale cultivar IAC 1 showed high grain yield in comparison to the other cultivars studied, and good adaptation to these soil conditions. The wheat cultivars IAC 5 and IAC 60 used as controls presented low productivity. The triticale cultivars IT 8029, TCEP 8136, ICT 8433, ICT 8437 and BR 2 showed high percentages of occurrence of sterile spikelets: above 50%. The triticale cultivar PFT 7882 exhibited the lowest percentage of sterile spikelets.
Keywords: grain yield; sterile spikelets; hydric balance